Lung metastases after liver cancer resection cured by immunotherapy: case report and literature review. Issue 1 (5th September 2022) - Ou, Limin; Lu, Guanhua; Cao, Mingrong; Hu, Min
Abstract : The lung is the most common metastatic organ of primary liver cancer, accounting for 39.5–53.8% of extrahepatic metastasis, which seriously affects the prognosis of patients. In clinical treatment, it is difficult for one therapeutic schedule to achieve the desired effect sometimes, requiring two or even several combined methods for liver cancer lung metastasis. In this study, we report a liver cancer patient with lung metastases who received various combined therapies. However, the comprehensive treatment did not improve the patient's pulmonary metastasis symptoms until after the application of immunotherapy, and the lung metastases were gradually cured.